The analysis of social and environmental factors in lung cancer patients - Słowik-Gabryelska, Anna; Sokołowski, Jarosław (Contemporary Oncology/Współczesna Onkologia, 2003)
The increasing number of lung cancer patients and continuously poor results of treatment make us intensify the prophylactic action. But it needs more in-depth epidemiological examinations to select the groups of inhabitants of the greatest lung cancer risk. Next, the set of carcinogenic factors, specific to each group and conditions influencing the lung cancer development ought to be recognised. These are the reasons for epidemiological examinations in regions of increased lung cancer incidence. The epidemiological examinations in 1 383 lung cancer patients were undertaken. All these patients were treated – in hospitals of the Włocławek province – between 1986–1995. The lung cancer morbidity dependence upon the gender, age, family burden of cancer, place of living, cigarette smoking habit, education, work and occupation was assessed. It was established – that in the analysed group 60% of lung cancer patients were men over 60.8% of patients were women, about 96% were smokers and among them more than 60% persons smoked over 20 cigarettes a day. In 21% of patients, lung cancer in relatives was seen, significantly more frequently in adenocarcinoma and anaplastic small cell carcinoma patients. 82% of lung cancer patients were low – educated blue collar workers. The lung cancer incidences was significantly higher in villagers, working in farms. The morbidity in that group was comparable to drivers and mechanics of cars only. In the province of Włocławek, persons of increased lung cancer risk include: poorly qualified blue collar workers, addicted to cigarette smoking. In that group lung cancer is significantly more frequent among in villagers working in farms, drivers and car mechanics and chemical industry workers. In conclusion it would be stressed, that in our area, persons of high lung cancer risk are heavy smoking men, of low socio-economic status, subjected to carcinogenic factors in the environment.